Abortion and contraception within prison health care: a qualitative study - Martha J. Paynter; Clare Heggie; Anja Mcleod; Wendy V. Norman (BMC Women's Health)
Abstract Background Although abortion was completely decriminalized in Canada 36 years ago, barriers to pregnancy prevention and termination persist across the country, such as travel and information gaps. Research demonstrates incarcerated people face barriers to family planning care, yet there is no systematic data collection of sexual and reproductive health experiences and outcomes among incarcerated people in Canada. The aim of this study was to explore family planning care experiences among women and gender diverse people who have experienced incarceration in Canada. Methods We conducted a qualitative community-based research study using focus groups for data collection and reflexive thematic analysis to generate key themes. Our study team included members with lived experience of incarceration. We conducted recruitment in partnership with community organizations. We asked about accessing abortion and contraception while incarcerated and on release. Results We conducted six focus groups with 35 recently incarcerated participants. Five themes emerged: (1) Competing health needs; (2) Institutional barriers to care; (3) Mistreatment and unethical care; (4) Health knowledge gaps; and (5) Challenges to care-seeking in community. Conclusion People in prison experience concurrent unmet health needs that crowd out sexual and reproductive health. Prison procedures and perceived unethical professional behaviours impinge care-seeking. Information about abortion and contraception is not readily available in prison. Barriers to care persist upon release. Family planning professionals may improve care for people who experience incarceration by recognizing concurrent mental health needs; anticipating impact of prior negative experiences on care-seeking; challenging limitations to health education in prison; and addressing post-release challenges for patients.